2013
DOI: 10.2106/jbjs.k.00734
|View full text |Cite
|
Sign up to set email alerts
|

The Military Extremity Trauma Amputation/Limb Salvage (METALS) Study

Abstract: Major lower-limb trauma sustained in the military results in significant disability. Service members who undergo amputation appear to have better functional outcomes than those who undergo limb salvage. Caution is needed in interpreting these results as there was a potential for selection bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(82 citation statements)
references
References 1 publication
1
80
0
Order By: Relevance
“…Over 20 years ago Giorgiadis, et al suggested that patients with a salvaged limb took longer to full weight-bearing, were less willing to work, had higher hospital charges, were more likely to consider themselves severely disabled, and had more problems with occupational and recreational activities [12]. More recently Doukas, et al (the METALS study) suggested that patients undergoing amputation had better functional outcomes than those undergoing limb salvage [11]. These findings are in contrast to Busse, et al, who performed a meta-analysis of observational studies comparing complex limb-salvage versus early amputation [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 20 years ago Giorgiadis, et al suggested that patients with a salvaged limb took longer to full weight-bearing, were less willing to work, had higher hospital charges, were more likely to consider themselves severely disabled, and had more problems with occupational and recreational activities [12]. More recently Doukas, et al (the METALS study) suggested that patients undergoing amputation had better functional outcomes than those undergoing limb salvage [11]. These findings are in contrast to Busse, et al, who performed a meta-analysis of observational studies comparing complex limb-salvage versus early amputation [7].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors report early amputation results in better functional outcomes, lower rates of post-traumatic stress disorder, and a higher likelihood to engage in sporting activities [11,27,31]. In contrast, patients who underwent delayed amputation had significantly higher rates of out-patients visits, wound complications, and infections [27].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to recognize that the similarities observed here and elsewhere, while encouraging, do not represent an absence of dysfunction or the full restoration of function in all people or across all aspects of life. Other deficits are often still present requiring further rehabilitation to restore function and quality of life [42].…”
Section: Russell Esposito Et Al Metabolic Demand Of Walking In Amputeesmentioning
confidence: 99%
“…In fact, up to 7-year follow-up of a large cohort of patients following severe lower extremity trauma has revealed no difference in self-reported functional outcome scores between patients who underwent limb salvage procedure versus amputation [113]. In a more recent cohort of 324 service members with severe lower extremity trauma, amputees actually had improved self-reported functional scores a higher likelihood of participating in sporting activities than those who underwent limb salvage [114].…”
Section: Amputationmentioning
confidence: 98%